An Analysis of Pap Smear Participation Among Health Workers Based on the Health Promotion Model - Linda Juwita; Ninda Ayu Prabasari; Pertiwi - Perwiraningtyas (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Health workers serve as role models, counselors, and educators in promoting preventive health behaviors. However, some female health workers still do not undergo Pap smear examinations as a cervical cancer prevention measure. This study aims to analyze the relationship between various factors and Pap smear participation among female health workers based on the Health Promotion Model. This research employed a quantitative analytical observational design with a cross-sectional approach. The population consisted of all female health workers at Gotong Royong Hospital Surabaya. A purposive sampling technique was used, involving 51 respondents who met the inclusion criteria. Independent variables included personal factors (age, perceived health, and culture), perceived benefits and barriers, self-efficacy, attitudes, interpersonal influences, husband support, and situational influences. The dependent variable was Pap smear participation. All variables were measured using questionnaires. Some of the questionnaires on independent variables were adopted from previous studies with reference to the Health Promotion Model theory. The results showed a significant relationship between age and participation in Pap smear screening among health workers, with a p-value of 0.006. However, no significant relationship was found for other variables. Age was found to be the only factor significantly associated with Pap smear participation. Future studies are recommended to use qualitative methods to explore deeper behavioral factors influencing Pap smear practices among health workers.